Cases of Human Visceral Leishmaniasis in the Municipality of Coité do Noia - AL, from 2013 to 2019, Brazil. - Oliveira Lira, Jeane de (2024)
Canine Leishmaniasis visceral is a common disease in countries of the Americas. In Brazil, its occurrence has been increasing in municipalities in the Brazilian Northeast due to the increase in the number of animals within the country, which may increase the number of animals infected by the protozoan Leishmania. The objective was to report the temporal trend and describe the distribution of incidence rates of Leishmaniose visceral in the municipality of Coité do Noia, state of Alagoas, from 2013 to 2019. An epidemiological survey was carried out in the State of Alagoas and in the municipality of Coité de Nóia - AL, from 2013 to 2019. The data used were obtained from the website of the Department of Informatics of the Sistema Único de Saúde (DATASUS), selecting the Leishmaniose Visceral item, the information was compiled from the number of cases notified in the region of Alagoas in Brazil. From 2013 to 2019, 15 cases of Leishmaniose Visceral were confirmed, with 2 deaths. There was a predominance of cases in women with 12 cases, and 4 for men. The study showed a higher occurrence for the municipality of Coite do Noia between 2018 and 2019 with prevalence for women.